Conociendo mi lateralidad izquierda derecha - Briones Rodriguez, Bertha Emerita (2019)
The present work of professional sufficiency it was done with the purpose of establish to what extent the application of the learning session: “knowing my left laterality right" whose ages are 4 years of the initial level where students developed globally cognitive, affective, and social aspects exploring the different movements of your body and the relationship with others where they can control their emotions, knowledge completed among themselves with their personality, self-esteem until reaching displacement and continue expanding their possibilities of movement and action. The students developed a progressive control and mastery of their body to organize themselves bodily according to their needs in the various daily situations of exploration in the games they experienced. Where they can interact with their environment where students build their body image and scheme; that is, he develops a mental representation of his body and an image of himself.